Outbreak - Peterson, Wolfgang (Philippines : Warner Bros, 1997)
The inhabitants of Cedar Creek. California are getting sick quickly. A lethal virus, for years safely contained with the depth of the African rainforest, has found it's way to this small community and is infecting its population. The virus might be anywhere. It is more deadly than the Black Plague and more contagious than the common cold...and it threatens to spread uncontrollable outwards. To neighbouring San Francisco throughout California,across the United States and, soon after around the world. Dr. Sam Daniels (Dustin Hoffman) is in a race against time to find the key that can stop the virus before it radiates beyond the small town and wipes out hundreds of thousands. He must also outpace his government superiors, who are poised to unleash a plan that will contain the virus in a manner as uncompromisingly lethal as the outbreak itself.